PERALIHAN STATUS KEPEMILIKAN TANAH WARISAN MENJADI TANAH PELABA PURA DALAM MASYARAKAT HUKUM ADAT BALI (STUDI KASUS DI DESA ADAT CANGGU) - Prabowo, Alim; Windia, I Wayan; Wirawan, I Ketut (Acta Comitas, 2017)
Someone who can be regarded as the heir is a person who fulfills the conditions and certain obligations that he is entitled to inherit. In connection with this case, it will be explained regarding liability issues of a child (swadharama). If someone gets inheritance but he has changed his religion then how does the inheritance status. The issue of this research is why the status of land ownership inheritance can be turned into Pelaba Pura land in balinese folks costumary law and how does the process of inheritance land ownership transfer into a Pelaba Pura land in balinese folks customary law in traditional village of canggu. Type of research used was empirical legal research conducted in the village of Canggu. It was a descriptive study. This study used primary and secondary data sources. Data collection techniques in this research were observation, interview and document study. Data processing and analysis techniques used in this study generally consisted of three stages of data analysis: data reduction, data display, and data verification stage. Results of the study on the considered problem was that the status of inheritance land ownership can be turned into Pelaba Pura land in in balinese folks costumary law because of religion change eliminates a person's status as a heir. Only descendants with Kapurusa status were deemed capable of taking care and continuing family’s Swadharma (responsibility), both in relation to parahyangan (Hindu’s belief), pawongan (Hindus), and palemahan (preservation of the natural environment in accordance with the Hindu’s belief). Thus it is the same as the person who left the family responsibilities (ninggal kedaton), and are therefore considered not entitled to inheritance in families. The ownership process of inheritance land that become Pelaba Pura land in customary law community of Canggu Bali. A single heir who has switched religions can no longer be regarded as an heir. Therefore disputed inheritance from the past until now has been dominated by Canggu custom banjar as pengemong and pengempon Khayangan temples of Canggu custom banjar hereditary. In this case the land is used as Pelaba Pura land which proposed sporadically. Existence of land belonging to the temple already has a legal basis, namely by the presence of Government Regulation No. 38 of 1963 On Legal institution to Have Properties of Land which was reaffirmed by the Decree of Home Affairs Ministry of Indonesia SK / 556 / DJA / 1986 on the appointment of Temple As a Religious Legal Entity That Can Have Reserved Land Rights.